Nitride bonded silicon nitride as a reusable crucible material for directional solidification of silicon. Issue 1 (10th September 2015) - Schneider, V.; Reimann, C.; Friedrich, J.; Müller, G.
Abstract : A nitride bonded silicon nitride crucible is reused six times for the directional solidification of undoped multicrystalline silicon ingots. The impurity content of the ingots can be clearly correlated to the impurity content of the NBSN crucible. The main ingot impurity is the acceptor B, which concentration decreases with continued reuse of the crucible. The contamination mechanism is most likely due to outdiffusion from the crucible wall into the Si melt. Abstract : Nitride bonded silicon nitride (NBSN) has the potential of a reusable crucible material for directional solidification of silicon. This is demonstrated in this work by reusing a NBSN crucible six times for the directional solidification of undoped multicrystalline (mc) silicon ingots. The progress of the ingot contamination at subsequent use of the NBSN crucible was studied systematically. Minority carrier lifetime, electrical resistivity as well as impurity content were analyzed after each solidification run. The results were compared to those obtained from ingots which were crystallized by using identical directional solidification process parameters in standard fused silica crucibles with silicon nitride coating. The impurity content of the ingots can be clearly correlated to the impurity content of the NBSN crucible. The main impurity is the acceptor B. Its concentration in the ingots decreases from about 10 17 atoms/cm 3 to 10 16 atoms/cm 3 with continued reuse. The contamination mechanism is most likely due to outdiffusion from the crucible wall into the Si melt.